Clinical outcomes of surgical treatment of transolecranon fracture-dislocation: a comparison between anterior and posterior types in a retrospective case series - Cha, Joo Young; Jung, Ki Jin; Nho, Jae-Hwi; Kim, Sung Hwan; Seo, Kun Il; Choi, Seung Won; Kim, Byung Sung (Archives of Hand and Microsurgery, 2025)
Purpose: Transolecranon fracture-dislocation is a rare and complex injury involving a fracture within the trochlear notch that causes ulnohumeral joint disruption. Due to its low incidence and the frequent misdiagnosis of ligament injuries, research on this injury is limited. This study aimed to analyze cases and surgical outcomes, classify injuries by displacement type (anterior vs. posterior), and determine the prevalence of ligament injuries.Methods: A retrospective analysis of 24 patients treated between 2005 and 2023 was conducted. Patients were categorized by displacement type into anterior (n=14) and posterior (n=10) groups. Associated injuries, surgical interventions, and postoperative outcomes were evaluated using range of motion (ROM), the Mayo Elbow Performance Index (MEPI), Disabilities of the Arm, Shoulder, and Hand (DASH) scores, and complication rates.Results: Posterior injuries demonstrated a higher incidence of radial head fractures (60% vs. 14.3%; odds ratio, 0.11; p=0.032) and ligament injuries than anterior injuries. Ligament injuries were more common than previously reported. Clinical outcomes were favorable, with a mean flexion-extension arc of 120.83°±7.69°, a MEPI score of 90.62±3.73, and a DASH score of 19.82±15.27. No significant differences in ROM or functional scores were observed between groups. Complications included heterotopic ossification (five cases), nonunion (three cases), and arthritic changes; however, no instances of postoperative instability were observed.Conclusion: Posterior injuries are more likely to involve radial head fractures and ligament injuries than anterior injuries. Ligament injuries should be considered, particularly in posterior injuries or cases with coronoid and radial head fractures. With thorough assessment and proper management, favorable functional outcomes can be achieved.